The Relationship Between Forgiveness and Happiness in Late Adolescents with Divorced Parents: A Correlational Study in Indonesia - Eunike Lisi Cintani Putri; Dewita Karema Sarajar (Universitas PGRI Yogyakarta, 2025)
This research explores the relationship between forgiveness and happiness in late adolescents from divorced families. With the increasing divorce rate in Indonesia, the psychological impact on children is a concern. The purpose of this study was to determine the relationship between forgiveness and happiness of late adolescents who have a divorced parent background. A quantitative correlational approach with measuring instruments used for forgiveness is the Transgression Interpersonal Motivation Inventory (TRIM-18) and happiness using the Oxford Happiness Questionnaire (OHQ involving 200 late adolescents aged 18-22 years across Indonesia. Data was collected through an online questionnaire measuring the level of forgiveness and happiness. Results showed a significant positive correlation (r = 0.492, p < 0.01), indicating that higher levels of forgiveness were related to greater happiness. This highlights forgiveness as an important psychological mechanism that helps adolescents turn negative experiences into personal strengths, improving their emotional well-being. Keywords: forgiveness, happiness, late adolescents, parent, divorce